Evaluation of the relationship between theory of mind relating to cognitive performance and post-traumatic stress disorder in Syrian refugee amputees living in Turkey. - TATAR, YAŞAR (My University, 2023)
Background According to the available literature, studies examining the relationship between theory of mind (ToM) and post-traumatic stress disorder (PTSD) have a small sample size and are few in number. Aims This study aims to investigate the relationship between the potential presence of PTSD in Syrian refugee amputees living in Turkey, ToM skills measured by Reading the Mind in the Eyes Test (RMET), and variables related to amputation. Method Our 69 follow-up amputee patients answered a socio-demographic and amputation data form, and the RMET, PTSD checklist for DSM-5 (PCL-5), and Beck Depression Inventory-II (BDI-II) completed a ToM task. Results Those with potential PTSD were signifcantly less educated than those without (p=.017). Prosthesis usage time (p=.002) and duration of post-amputation (p=.033) were signifcantly shorter in those with potential PTSD compared to those without. The RMET neutral valence (p=.035) and RMET total (p=.017) accuracy scores were signifcantly lower in patients with potential PTSD. Those with potential PTSD were higher signifcantly more depressed (p<.001). In our regression analyses, lower education level (p<.05), shorter prosthesis usage time (p=.008), and lower RMET neutral valence (p=.006) / RMET total (p=.032) accuracy scores predicted the presence of potential PTSD. Conclusions Lower education level, prosthesis use for a shorter period, and poor mind-reading skills from neutral and total eye expressions were predictive of the potential presence of PTSD in amputees, even though they were largely exposed to similar traumas. Our fndings suggest that treatment and follow-up of PTSD should also target defcits in cognitive and emotional abilities.
Keywords: Sosyal ve Beşeri Bilimler; Sağlık Bilimleri; Social Sciences and Humanities; Health Sciences; Klinik Tıp (MED); Sosyal Bilimler (SOC); Clinical Medicine (MED); Social Sciences (SOC); Amputee; PTSD; Refugee; Theory of mind; Trauma